2016
DOI: 10.1080/15226514.2016.1183566
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacterial communities associated with Brassica napus L. growing on a Zn-contaminated soil and their effects on root growth

Abstract: The interaction between plant growth-promoting bacteria (PGPB) and plants can enhance biomass production and metal tolerance of the host plants. This work aimed at isolating and characterizing the cultivable bacterial community associated with Brassica napus growing on a Zn-contaminated site, for selecting cultivable PGPB that might enhance biomass production and metal tolerance of energy crops. The effects of some of these bacterial strains on root growth of B. napus exposed to increasing Zn and Cd concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…Other PGPB, such as the Gram‐negative Pedobacter , is also capable of colonizing roots of many crop plants, e.g. potato and oilseed rape, and could be used as a biofertilizer. However, its effects on photosynthetic mechanisms, yield and growth of plants are poorly documented.…”
Section: Introductionmentioning
confidence: 99%
“…Other PGPB, such as the Gram‐negative Pedobacter , is also capable of colonizing roots of many crop plants, e.g. potato and oilseed rape, and could be used as a biofertilizer. However, its effects on photosynthetic mechanisms, yield and growth of plants are poorly documented.…”
Section: Introductionmentioning
confidence: 99%
“…ACC deaminase activity can reduce the ethylene levels generated due to stress, improving the growth of plants in presence of toxic concentrations of metals [ 16 ]. It is important to mention that the endophytic bacterial strains that increased the growth of H. tuberosus also increased the length of the roots of Brassica napus seedlings in vertical agar plates containing toxic concentrations of Cd and Zn [ 24 ]. This suggests that these endophytes are beneficial for plants from different families.…”
Section: Resultsmentioning
confidence: 99%
“…This leads to a reduced metal uptake and translocation inside the plant, improving its growth through decreasing phytotoxicity [ 8 , 23 ]. In a previous study, we showed that bacterial strains isolated from a Zn contaminated soil increased root length of Brassica napus seedlings in the presence of Cd and Zn under in vitro conditions [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are no earlier reports about the isolation of endophytic and rhizospheric bacteria from this plant species. Though, there exist many studies reporting the isolation of trace element tolerant bacteria from other species such as Arabidopsis [31], Brassica napus [32,33], Thlaspi (syn. Noccaea) caerulescens [34], Nicotiana tabacum [35].…”
Section: Discussionmentioning
confidence: 99%